2014
DOI: 10.1007/s00592-014-0697-5
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide reduction in the frequency of severe hypoglycemia by half

Abstract: A nationwide halving in rates of severe hypoglycemia was observed during the study period independent of the prevailing average HbA1c level. Changes in diabetes care and successful educational programs may have influenced the lower incidence rate of severe hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 21 publications
6
59
1
Order By: Relevance
“…Hypoglycemia is a common disorder among diabetic patients, which may be reducing due to changes in diabetes care and success of educational programs [32]. It does not always result in hospitalization; therefore, it is possible that Analyses adjusted for calendar period, sex and age at T1D diagnosis Acta Diabetol the number of events identified in our study may represent an underestimate.…”
Section: Discussionmentioning
confidence: 70%
“…Hypoglycemia is a common disorder among diabetic patients, which may be reducing due to changes in diabetes care and success of educational programs [32]. It does not always result in hospitalization; therefore, it is possible that Analyses adjusted for calendar period, sex and age at T1D diagnosis Acta Diabetol the number of events identified in our study may represent an underestimate.…”
Section: Discussionmentioning
confidence: 70%
“…During that period a large increase in patients on pump therapy was observed. 9 However, the SH rate in Sweden was stable and low (between 2 and 5 per 100 patient-years) and in Norway the SH rate was stable at a higher level (between 7 and 10 per 100 patient-years), despite a lower percentage of patients using insulin pump in Sweden compared with Denmark and Norway. When analyzed in toto, there appeared to be an association between insulin pump use and lower rates of SH; however, this association was not consistently seen across individual countries nor did it explain the variance in rates of sever hypoglycemia between countries.…”
Section: Pathophysiology/complicationsmentioning
confidence: 94%
“…[8][9][10] In the same period, an increased number of BG measurements and insulin bolus injections have been recommended. 3 These changes may all contribute to reduce the frequency of SH.…”
Section: Pathophysiology/complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of more recent studies have not confirmed the strong association between optimization of glycemic control and an increase in risk of SH in children, adolescents, and adults. [18][19][20][21][22][23][24] Nevertheless, CGM might be a technical solution assisting the achievement of both treatment goals. It is of interest to note that in a recent publication no indication was found that CGM usage reduces SH, fear of hypoglycemia, hypoglycemia awareness, or even biochemical hypoglycemia.…”
Section: Risk Of Hypoglycemic Events In Patients With Type 1 Diabetesmentioning
confidence: 99%